Հայաստանի ազատագրության խնդիրն ըստ Պետրոս Պետիկի «Cehil Sutun» գրքի - Ավետիսյան, Զինա (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
The prospect of forming anti-Turkish alliance forced Shah Abas to open the doors of his country to catholic missionaries. The Armenian environment could become fertile ground for their activities. The catholic church which had not been achieving any significant result for about 5 years, sent Jesuits to the East. Jesuits were the most intolerant and active group of Catholics. One of the Jesuit missionaries was Armenian-born Pedros Bedik, who had graduated from Urban Collage. Soon he arrived to Persia as an assistant of Matheos Hovhanisets who had brought letters for Shah Suleiman from Pope and European emperors. Bedik, about his journey to Iran, wrote an important Latin book entitled “Cehil Sutun”. The far-reaching idea of liberation of Armenia brought Bedik and Hakob Jughayetsi closer. After long-time negotiations they reached a common agreement and soon Bedik and Piskop, who was an envoy of Shah, took the letters of Catholicos addressed to emperior Leopold I and Pope. Bedik, as a delegate of Armenian Patriarch, presented the situation of Armenia and had a discussion with the Catholic leaders. In his work Bedik presented the vision of Catholicos for the liberation of Armenia and helped to draw conclusions about the approaches and existing intentions to gain independence. It gives an opportunity to value Hakob Jughayetsi anew as a forerunner of the liberation movement and Patriarch concerned with the fate of his nation.
Keywords: Պատմություն